José Antonio Suárez: a private matter - González de Ripoll, Beatriz (Estudios de Filosofía, 2000)
This paper considers several aspects of the works of José Antonio Suárez, catalogued as small format and micrography. The reasons for the attraction exerted by the minimal are considered: the perfection of the jewel, the magic of talisman, the craft, the trick, the publishing models of the illustrations. It is also studied the use of the intimacy involved in the diary, the rejection to produce big Art and at the same time the admiration towards the Art of museums. Finally, the possibilities offered by the small format to the engraving are studied.